2020
DOI: 10.1177/1461355720905612
|View full text |Cite
|
Sign up to set email alerts
|

Patriarchal beliefs and perceptions towards women among Indian police officers: A study of Uttar Pradesh, India

Abstract: The objective of this study was to explore the association between patriarchal beliefs and perceptions regarding gender equity among Indian police officers. Using convenience and systematic random sampling, a cross-sectional survey was conducted with 190 police officers from Allahabad, Uttar Pradesh, India. The survey collected information about patriarchal beliefs, perception regarding gender equity, as well as social demographic characteristics including age, education, gender, work experience, working shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Moreover, police officers in India are sometimes accused of sexually assaulting women, particularly sex workers (Chettiar 2015;Erausquin et al 2011). For these reasons, many scholars suggest that Indian police agencies need to hire more women (e.g., Tripathi 2020). Moreover, some Indian police agencies have established police stations staffed entirely by women.…”
Section: Crimes Against Womenmentioning
confidence: 99%
“…Moreover, police officers in India are sometimes accused of sexually assaulting women, particularly sex workers (Chettiar 2015;Erausquin et al 2011). For these reasons, many scholars suggest that Indian police agencies need to hire more women (e.g., Tripathi 2020). Moreover, some Indian police agencies have established police stations staffed entirely by women.…”
Section: Crimes Against Womenmentioning
confidence: 99%
“…Since male-dominated professions such as law enforcement tend to espouse strong patriarchal beliefs (Tripathi, 2020), many police officers may exhibit sexist attitudes, originating from the societal myths of gender inequality and patriarchy . Previous studies have indicated that police officers with sexist attitudes view IPV as an ordinary and private matter, and prosecute perpetrators only when victims insist on doing so (Gölge et al, 2016; Lila et al, 2013); this further demonstrates that ambivalent sexism, which can be defined as attitudes toward women, consisting of two factors: “hostile sexism (HS),” which is overtly negative attitudes toward women, and “benevolent sexism (BS)” which views women as an inferior gender that require protection (Glick & Fiske, 1996), is related to attitudes and behavior with respect to IPV (Allen et al, 2009; Anderson & Anderson, 2008; Glick et al, 2002; Renzetti et al, 2018).…”
mentioning
confidence: 99%